Molecular phylogeny of Macrobrachium species of India: habitat preference, biogeography and taxonomy - Parhi, Janmejay; Lakra, W. S.; Mazumdar, Kshitish; Sahoo, Lopamudra; Gon Choudhury, Tanmoy (Indian Journal of Fisheries, 2014)
The freshwater prawn genus Macrobrachium (Bate) is one of the most diverse, abundant and widespread crustacean genera. Different species of this genus have different habitat preference, as some species require access to the sea during their larval development whereas some species are restricted to inland waters with abbreviated larval development. The greatest diversity of the genus occurs in the Indo-Pacific region, in particular the Indian subcontinent. To examine the phylogenetic relationships of Macrobrachium species of this region with reference to their habitat preference, biogeography and taxonomy, the cytochrome b gene of mitochondrial DNA was amplified and sequenced. Based on the phylogenetic investigation, it was found that the species having same habitat preference were close to each other. However based on the genetic distance and nucleotide difference, it was further observed that species restricted to Indian subcontinent shared close relationship irrespective to their habitat preference leading to the conclusion that preference of habitat for reproductive strategy has evolved independently within a particular geographical area.